Experimental Heat Transfer, Sound Insulation and Interior Comfort Parameters Assessment on a Box Double-Skin Façade - Năstase, G.; Doboși, I.S.; Brezeanu, A.I.; Taus, D.; Tăbăcaru, M.B.; Vuțoiu, B.G.; Rusu, D.; Bulmez, A.M.; Iordan, N.F. (MDPI, Basel, Switzerland, 2022)
The envelope (façade) of a building is the part that forms the primary barrier to its environment. Most of the new and modern office buildings have a glazed envelope and are usually built-in city centers. The concept of a double-skin façade was born as a consequence of urban noise. The principal noise source in urban areas is traffic noise. Using a double-skin façade can be a solution that ensures good sound insulation for a glazed office building. This study presents experimental results obtained both from measurement campaigns carried out over longer periods of time, in connection with heat transfer in the case of this system, and punctual measurements, over shorter periods of time, for sound insulation and interior comfort parameters, from the experimental chamber adjacent to the system. The results from this study indicate that box double-skin façades can contribute to noise reduction, improve the interior thermal comfort and increase the energetic performance compared to normal single-glass façades, but within certain limits.